A Study of Carl Rogers' Humanist Approach in Interfaith Counseling - Fredrik Y. A. Doeka; Saartje Banja (Millah: Journal of Religious Studies, 2022)
This article analyzes counseling services to counselees of different churches and religions. The main objective is to answer whether there is a possibility that counselees from different churches and religions will be helped. The research was conducted using a qualitative method in which we focused on descriptive data that refers to the counselee's spoken words and behavior. The research was conducted at the Yayasan Tembok Ratapan Timor, Kupang,  Nusa Tenggara Timur, Indonesia. The Study found that counselees from various churches and religions can solve their problems when their potential is revealed. The humanist approach of Carl Rogers used by the counselor is very effective in maximizing the counselee's potential. Through a review of religions' theology, it was concluded that the love of God deserves to be enjoyed by counselees of different religions.